Modeling and Simulation of Moisture Transmission through Fibrous Structures Part I: Water Vapour Transmission (Journal of Fiber Bioengineering and Informatics, 2012)
The moisture transmission behaviour of clothing plays an important role in determining its thermo-physiological comfort. The determination of the factors involved in moisture transmission of clothingand its prediction have become a main concern for researchers for many years. An attempt has beenmade to review the research studies on modeling and simulation of moisture transmission through fibrousassemblies. The review work has been divided in two parts. The first part deals with moisture vapourtransmission and the second with liquid water transmission through fibrous materials. The variousprocesses involved in water vapour transmission through fibrous materials are diffusion, absorption -desorption, convection, evaporation and condensation. The models on water vapour transmission throughfibrous materials are based on the mass balance equation. Some of the studies involving theoretical workon vapour transmission have been conducted on individual processes. Others consider the inter-relatedeffects involved. Moisture vapour transmission through textile materials is coupled with heat transferphenomena, due to its hygroscopic nature. The atmospheric conditions, the structure of the fibrousmaterials and the hygroscopic nature of the fibres significantly influence the processes. Amongst theavailable models on vapour transmission, the model developed by Li and Zhu predicts simultaneousheat and moisture transfer considering moisture sorption, condensation and capillary liquid diffusion inporous textiles and this model is best suited for determining textile clothing comfort.